PRACTICAL SIGNIFICANCE OF USING THE ALGOLIZATION PROCESS IN THE FIELDS OG AGRICULTURE AND BIOLOGY (Modern American Journal of Biological and Environmental Sciences, 2025)
This article provides a scientific analysis of the practical significance of utilizing the algolization process in agriculture and biology. Research demonstrates that applying the biomass of microalgae such as Chlorella vulgaris, Spirulina platensis, and Scenedesmus obliquus to soil and plants can enhance soil and crop productivity, increase plant growth rates, and improve stress tolerance. The algolization process is evaluated as an important tool for improving soil fertility, increasing biological activity, and ensuring environmentally safe agricultural production.